Received Signal Strength Based Target Localization and Tracking Using Wireless Sensor Networks - Jondhale, Satish R.; Maheswar, R.; Lloret, Jaime; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book briefly summarizes the current state of the art technologies and solutions for location and tracking (L&T) in wireless sensor networks (WSN), focusing on RSS-based schemes. The authors offer broad and in-depth coverage of essential topics including range-based and range-free localization strategies, and signal path loss models. In addition, the book includes motion models and how state estimation techniques and advanced machine learning techniques can be utilized to design L&T systems for a given problem using low cost measurement metric (that is RSS). This book also provides MATLAB examples to demonstrate fundamental algorithms for L&T and provides online access to all MATLAB codes. The book allows practicing engineers and graduate students to keep pace with contemporary research and new technologies in the L&T domain. Presents a variety of perspectives on real time location and tracking (L&T) problems and low cost solutions; Allows readers to simulate L&T systems and validate them using real time measurements; Includes MATLAB based examples, codes and illustration of obtained results.
Chapter 1 . Fundamentals of Wireless Sensor Networks -- Chapter 2. Target Localization and Tracking using WSN -- Chapter 3. Survey of Existing RSSI Based Target L&T Systems -- Chapter 4. Trilateration Based Target L&T Using RSSI -- Chapter 5. KF Based Target L&T Using RSSI -- Chapter 6. GRNN Based Target L&T Using RSSI -- Chapter 7. Supervised Learning Architectures Based Target L&T Using RSSI.
Keywords: Telecommunication; Cooperating objects (Computer systems).; Software engineering; Communications Engineering, Networks; Cyber-Physical Systems; Software Engineering; Wireless localization; Wireless sensor networks